The impact of business group affiliation on performance: evidence from China's 'national champions' - Guest, Paul M.; Sutherland, Dylan (Oxford University Press, 2010)
An important aspect of China's economic reforms has been an ambitious policy to develop 100 or so large, internationally competitive business groups. Very little is known about these national champion groups or the benefits to subsidiary firms of belonging to them. This study, building from insights and methods used in existing literature, examines the performance of subsidiaries affiliated to China's national champion groups. Our results find that they perform comparatively well. We discuss possible reasons for this finding and comment more generally on the important role that business groups now play in China's reform and development.